Effectiveness of UV-C light assisted by mild heat on Saccharomyces cerevisiae KE 162 inactivation in carrot-orange juice blend studied by flow cytometry and transmission electron microscopy - García Carrillo, Mercedes (2018)
The aim of this study was to analyze the effectiveness of UV-C light (0–10.6 kJ/m2) assisted by mild heat treatment (50 °C) on the inactivation of Saccharomyces cerevisiae KE 162 in peptone water and fresh carrot-orange juice blend (pH: 3.8; 9.8°Brix; 707 NTU; absorption coefficient: 0.17 cm−1). Yeast induced damage by single UV-C and mild heat (H) and the combined treatment UV-C/H, was investigated by flow cytometry (FC) and transmission electron microscopy (TEM). When studying induced damage by FC, cells were labeled with fluorescein diacetate (FDA) and propidium iodide (PI) to monitor membrane integrity and esterase activity. UV-C/H provoked up to 4.7 log-reductions of S. cerevisiae; whereas, only 2.6–3.3 log-reductions were achieved by single UV-C and H treatments. FC revealed a shift with treatment time from cells with esterase activity and intact membrane to cells with permeabilized membrane. This shift was more noticeable in peptone water and UV-C/H treated juice. In the UV-C treated juice, double stained cells were detected, suggesting the possibility of being sub-lethally damaged, with compromised membrane but still metabolically active. TEM images of treated cells revealed severe damage, encompassing coagulated inner content, disorganized lumen and cell debris. FC and TEM provided additional information regarding degree and type of damage, complementing information revealed by the traditional plate count technique.